2013
DOI: 10.1038/cdd.2013.7
|View full text |Cite
|
Sign up to set email alerts
|

The E3 ligase PIRH2 polyubiquitylates CHK2 and regulates its turnover

Abstract: The serine threonine kinase checkpoint kinase 2 (CHK2) is a DNA damage checkpoint protein important for the ATM-p53 signaling pathway. In addition to its phosphorylation, CHK2 is also ubiquitylated, and both post-translational modifications are important for its function. However, although the mechanisms that regulate CHK2 phosphorylation are well established, those that control its ubiquitylation are not fully understood. In this study, we demonstrate that the ubiquitin E3 ligase PIRH2 (p53-induced protein wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
37
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 46 publications
(40 citation statements)
references
References 40 publications
(67 reference statements)
1
37
0
1
Order By: Relevance
“…36 Our most recent study of Pirh2 −/− mice revealed an increase in Chk2 levels both under unstressed conditions and following DNA damage. 7 Despite the similar level of expression and activation of Atm in the absence or presence of Pirh2, γ-irradiation resulted in higher phosphorylation levels of p53 and E2F1, 2 Chk2 substrates in Pirh2 −/− cells compared with wild-type controls. This finding suggested the possibility that accumulated Chk2 in Pirh2 −/− cells might be due to defective ubiquitylation of this kinase.…”
Section: Pirh2 and Chk2mentioning
confidence: 99%
See 4 more Smart Citations
“…36 Our most recent study of Pirh2 −/− mice revealed an increase in Chk2 levels both under unstressed conditions and following DNA damage. 7 Despite the similar level of expression and activation of Atm in the absence or presence of Pirh2, γ-irradiation resulted in higher phosphorylation levels of p53 and E2F1, 2 Chk2 substrates in Pirh2 −/− cells compared with wild-type controls. This finding suggested the possibility that accumulated Chk2 in Pirh2 −/− cells might be due to defective ubiquitylation of this kinase.…”
Section: Pirh2 and Chk2mentioning
confidence: 99%
“…Interestingly, concomitant loss of Chk2 completely rescued this phenotype suggesting that increased Chk2 levels and activity were responsible for this hyperactivation of the cell cycle checkpoints. 7 …”
Section: Pirh2 and Chk2mentioning
confidence: 99%
See 3 more Smart Citations